Computational intelligence in healthcare : applications, challenges and management - Gupta, Meenu, (Professor of computer science) (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2023)
"Computational intelligence (CI) refers to the ability of computers to accomplish tasks that are normally completed by intelligent beings such as humans and animals. Artificial intelligent systems, offers great improvement in healthcare system by providing more intelligent and convenient solutions and services assisted by machine learning, wireless communications, data analytics, cognitive computing, and mobile computing. Modern health treatments are faced with the challenge of acquiring, analyzing and applying the large amount of knowledge necessary to solve complex problems. AI techniques are being effectively used in the fields of healthcare system by extracting the useful information from the vast amounts of data by applying Human expertise and Computational intelligence (CI) methods such as fuzzy models, artificial neural networks, evolutionary algorithms, and probabilistic methods which have recently emerged as promising tools for the development and application of intelligent systems in healthcare practice. This book starts with the fundamentals of computer intelligence and the techniques and procedures associated with it. Contained in this book are state-of-the-art methods of computational intelligence and other allied techniques used in the healthcare system, as well as advances in different CI methods that will confront the problem of effective data analysis and storage faced by healthcare institutions. The objective of this book is to provide the latest ongoing research related to healthcare sector to the researchers and engineers with a platform encompassing state-of-the-art innovations; research and design; implementation of methodologies"--
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Medical applications; Medical technology; COMPUTERS / Artificial Intelligence